Розробка та застосування алгоритму швидкої обробки зображення для систем візуалізації біо- та хемілюмінесценції - Калмиков, О. С. (ХНУРЕ, 2021)
The report discusses the possibility of using an algorithm for fast image analysis in order to determine the coordinates of the object under study on it. The use of this type of algorithms can be used to visualize processes in the luminescence analysis of biological systems.
Keywords: обробка зображення; система візуалізації